Future Time Orientation Scale: Psychometric Properties in a Sample of Brazilian Adolescents - Gibril Ussif; Lucy Leal Melo-Silva; Vinicius Coscioni (Revista de Psicología, 2025)
The Future Time Orientation Scale (FTOS) is a measure that assesses the extent to which a person is impacted by their psychological future. Several validity and reliability evidence for the FTOS have been investigated in the Brazilian and Portuguese context based only on adult samples. Considering that future time orientation is sensitive to age differences, the validity and reliability of the FTOS among adolescents cannot be ensured based on studies with adults. Thus, the purpose of this study is to assess the psychometric properties of the FTOS in a sample of Brazilian adolescents. In total, 262 individuals aged between 14 and 19 years old filled in the FTOS in a survey conducted in two public schools in Ribeirão Preto/SP, Brazil. Confirmatory factor analysis demonstrated that the FTOS original version well-fitted the data, consistently outperforming an alternative unidimensional model. The internal consistency achieved mostly acceptable values. The scale is not affected by ceiling or floor effect. Correlations to life project endorsed validity evidence based on the relations to other measures. Measurement invariance models comparing the sample of this study with a sample of adults demonstrated metric invariance, with two intercepts being different across age groups. Based on the findings, the FTOS is a valid and reliable measure to assess FTO among adolescents, though intercept differences may bias comparisons with adults.